The Influence Of Cash Conversion Cycle Toward Bankruptcy Risk Using Altman Z-Score - Andoko; Santana, Sindy (Cattleya Darmaya Fortuna, 2025)
This study investigates the impact of the cash conversion cycle (CCC) on bankruptcy risk in manufacturing companies listed on the Indonesia Stock Exchange (BEI) from 2019 to 2023, using Altman Z-Score as a measure of bankruptcy risk. The sample, selected through purposive sampling, includes 231 observations from companies meeting specific criteria. Multiple linear regression analysis is employed, with CCC as the main independent variable and control variables including current ratio (CR), return on assets (ROA), company size (SIZE), and debt-to-equity ratio (DER). Classical assumption tests ensure the reliability of the regression model. The findings indicate that CCC significantly affects bankruptcy risk, suggesting that effective CCC management can reduce bankruptcy likelihood. ROA, SIZE, and DER also significantly influence bankruptcy risk, while CR shows no effect. This research highlights the importance of optimizing CCC through improved inventory and receivables management to maintain financial stability. CCC is also a valuable indicator for investors in assessing a company’s financial health. Future studies should explore additional variables and adopt alternative analytical methods to enhance insights.